Inter-laboratory comparison of a serum fibroblast growth factor receptor 3 (FGFR3) antibody test in sensory neuropathies - Appeltshauser, Luise; Moritz, Christian P.; Reinhardt, Lena; Kreß, Luisa; Üçeyler, Nurcan; Lassablière, François; Barcic, Anastasia; Seefried, Sabine; Sommer, Claudia; Tholance, Yannick; Antoine, Jean-Christophe; Camdessanché, Jean-Philippe; et al. (Frontiers in Immunology, 2025)
IntroductionAutoantibodies against fibroblast growth factor receptor 3 (FGFR3) have been suggested as a diagnostic marker in both sensory large and small fiber neuropathy. Yet, their clinical relevance remains unclear and no standardized protocols for antibody testing exist. Here, we evaluate an anti-FGFR3 ELISA protocol in an inter-laboratory comparison.MethodsWe performed anti-FGFR3 ELISA on 42 serum samples of patients with sensory neuronopathy (n = 18), small fiber neuropathy (n = 18), and healthy controls (n = 6) in two independent centers in France (center 1) and Germany (center 2) using identical protocols, with double immunofluorescence staining on rat dorsal root ganglion (DRG) sections as a confirmational test.ResultsOverall ELISA concordance was 34/42 (81.0%, Cohen’s kappa = 0.61, substantial agreement). Discordance occurred for sera with optical densities (OD) near the cut-off. ODs correlated (r = 0.68, p < 0.0001), but were lower at center 2 (median = 0.076 vs 0.293, p < 0.0001), indicating that cut-off values are laboratory-specific. 11/16 (68.8%) ELISA-double-positive sera stained small DRG neurons, colocalizing with commercial anti-FGFR3 antibody, while positive binding was only found in 1/20 (5%) of ELISA-negative sera (p < 0.0001). DRG-positive samples showed higher ODs than negative ones (p < 0.0001).DiscussionWe provide and evaluate a detailed ELISA protocol for anti-FGFR3 diagnostic assessment. Positive results near the threshold should be interpreted cautiously. Anti-FGFR3 DRG staining may be a useful confirmatory method and could increase diagnostic specificity. This study facilitates future studies on the diagnostic relevance of anti-FGFR3 autoantibodies in sensory neuropathies.